Nathalie Sarraute au croisement des cultures - Modrzejewska, Krystyna (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Nathalie Sarraute (1900-1999) was born in Russia but she lived in France. She was a writer, a woman of immense erudition, and a polyglot whose works show the experience of a tragic ‘Me’ fighting against ‘the Other’. The consequences of the childhood spent abroad, far from her grandparents whom she loved very much; the holidays spent in Russia; her expectation of the promised meeting with her mother; her being defenceless against her stepmother; finally, the awareness that her strange surroundings was a threat: all these factors made her censor her own words and understand the importance of contact with the Other. This painful experience of childhood and living at the crossing of cultures, became a very rich and interesting literary substance expressed through so-called tropisms. From her first work to the last one, the author’s most important aim is to deal with the mechanisms that generate concrete statements, like pre-dialogue or under-conversation; she is interested with all kinds of reflective activity caused by the fear of an unwanted reaction to what we say.